(untitled) (Texas Journal of Philology, Culture and History, 2023)
The debatable question of the correlation of related linguistic concepts (text and discourse), which is of fundamental importance for the most consistent and consistent interpretation of them, is considered. An attempt is made to identify this relationship through the determination of the concepts of text and discourse in the system of language/speech. A definition of discourse in line with the issue being addressed is proposed.